CHARACTERISTICS OF GROWTH AND PRODUCTION OF KAILAN (BRASSICA OLERACEAE L.) IN SOME SOIL ORIGIN THROUGH CASGOT GRANTING AND BIOCHAR RICE HUSKS - Syahputra, Ardi; -, Lisdayani (Universitas Quality, 2023)
Kailan plants are spread in Southeast Asia, West and East Africa, West India, and some tropical areas. Kailan entered Indonesia around the 17th century, but this vegetable is quite popular and in demand among the people, so it has quite good marketing prospects. Commercial vegetable business and development can be considered as one of the efforts to increase income in agriculture. Kailan has a fairly high nutritional content, namely in every 100 grams of your raw material it contains 3500 IU of vitamin A, 0.11 mg of vitamin B1, 90 grams of water, 3.6 grams of fat, 1.6 mg of niacin, 78.0 mg of calcium , 1.0 mg of iron, 38.0 mg of magnesium and 74.0 mg of phosphorus. Organic farming systems besides having a good impact on health and the environment, also have a higher selling value when compared to organic farming. Organic fertilizer is an important element that can increase agricultural production and productivity in Indonesia.BSF has a variety of symbiotic bacteria including Bacillus sp. Which is useful as a plant pathogen control agent. In addition, these bacteria are also useful as rhizobacteria which promote plant growth. The application of organic fertilizers to the soil is intended as a soil enhancer (amelioran) to improve the physical, chemical and biological fertility of the soil in the long term. The main challenge that hinders the use of organic fertilizers is the limited sources of organic matter, as most organic resources have other competing uses such as feeding livestock on farms. The purpose of this study was to determine the effect of cassava fertilizer and rice husk Biochar on the growth and production of kailan plants in soil origin. The research was conducted at the Experimental Garden of the Faculty of Agriculture, University of Al-Washliyah Medan, in Simalingkar B with a height of ± 18 meters above sea level. The time of the research will start from July to August 2023. This research uses a Randomized Factorial Group Design which consists of 2 factors, namely: Factor I. Origin of Land (T) T1 = Origin of Langkat Regency, T2 = Origin of Deli Serdang Regency, T3 = Origin of Regency Labuhan Batu. Factor II. Application of Kasgot and Rice Husk Biochar (dose of 15 tons/ha) A0 = Control, A1 = Biochar 25% + Kasgot, A2 = Biochar 50% + Kasgot. The results showed that the use of cassava fertilizer and rice husk biochar along with some soil origins had a significant effect on plant height, stem diameter, number of leaves and wet weight. The highest height of kailan plants was in treatment A1 (75 grams of rice husk biochar and 25 grams of cassava) which was 18.44 cm and the wet weight of kailan plants was 6.89 grams. stone harbor (T3) and Sampali soil (T2).